(untitled) (Journal of Hama University, 2024)
The aim of this research was to investigate the effect of sodium hypochlorite gel application on bond strength of composite to enamel of primary teeth after salivary contamination following the application stage of the bonding material. Methods: The sample included 50 recently extracted primary human teeth. The sample was randomly distributed into 5 groups: The control group (A), included 10 primary teeth, composites were applied in the traditional manner without any salivary contamination. The second group (B) consisted of 10 primary teeth, where salivary contamination was applied after the application of bonding material, rebonding and followed by the application of composite. The third group (C) included 10 primary teeth, which salivary contamination was applied after the application of bonding material, drying and followed by the application of composite. The fourth group (D) included 10 primary teeth, which salivary contamination was applied after the application of bonding material, application of sodium hypochlorite gel and followed by the application of composite. The fifth group (E) included 10 primary teeth, which salivary contamination was applied after the application of bonding material, application of sodium hypochlorite solution and followed by the application of composite. Results: It was observed that the mean bonding strength values for the enamel groups in the research sample were as follows: (A=13.36 Mpa)> (C=11.80 Mpa) >(E=8.22 Mpa) >(D=7.42 Mpa)> (B=5.74 Mpa) Conclusion: We conclude that the application of sodium hypochlorite gel after salivary contamination decrease the composite bonding strength to enamel teeth.